2013
DOI: 10.1177/1352458513495584
|View full text |Cite
|
Sign up to set email alerts
|

The link between resting-state functional connectivity and cognition in MS patients

Abstract: Objective: The objective of this paper is to explore differences in resting-state functional connectivity between cognitively impaired and preserved multiple sclerosis (MS) patients. Methods: Sixty MS patients and 18 controls were assessed with the Brief Repeatable Battery of Neuropsychological Tests (BRB-N). A global Z score of the BRB-N was obtained and allowed us to classify MS patients as cognitively impaired and cognitively preserved ( n = 30 per group). Functional connectivity was assessed by independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 37 publications
3
61
0
2
Order By: Relevance
“…38 The FPN has been associated with executive task performance 39 and its connectivity decreases, for example, in patients with multiple sclerosis who frequently present with impaired executive functions. 40 Corresponding to lower RSFC in these networks, both episodic memory and executive scores were lower in our patients group compared with controls. In sum, we provide evidence that unilateral decreases of VMR are characterized by both ipsilateral and bilateral alterations in connectivity between major nodes of the DMN and the FPN.…”
Section: Discussionmentioning
confidence: 62%
“…38 The FPN has been associated with executive task performance 39 and its connectivity decreases, for example, in patients with multiple sclerosis who frequently present with impaired executive functions. 40 Corresponding to lower RSFC in these networks, both episodic memory and executive scores were lower in our patients group compared with controls. In sum, we provide evidence that unilateral decreases of VMR are characterized by both ipsilateral and bilateral alterations in connectivity between major nodes of the DMN and the FPN.…”
Section: Discussionmentioning
confidence: 62%
“…Increased FC has previously been understood as a secondary neuropathological sign of MS progresion [14] or as a compensatory mechanism for early MS neuropathological changes [12,13]. Only the later interpretation would be coherent with several additional findings of our study: 1) the direct correlation found between FC and GM atrophy; 2) the fading gender-related differences in FC when GM volume was introduced as a covariate; 3) lack of differences in neurological and neuropsychological performance (see Table 1) between Male-and Female-MSp despite their different degrees of GM atrophy in several brain regions; 4) the positive association of remaining GM volume and FC scores with attentional capabilities in Male-but not in Female-MSp.…”
Section: Discussionmentioning
confidence: 99%
“…Increased FC resulting from GM atrophy in MS patients has been interpreted in two different ways: Either as maladaptive and, as such, a sign of MS neuropathological progression [14] or, to the contrary, as a compensatory mechanism promoting normal cognitive competence of MS patients at initial stages of the disease [12,13]. To find out which of these two alternatives applies to our observations, we analyzed the relationship between FC, GM volume and cognitive performance in Male-and Female-MSp.…”
Section: Functional-cognitive Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a growing number of studies have revealed that MS patients might retain apparently normal cognitive performance by increasing the number of neural resources, at least in early stages of the disease [8,9,10,11,12]. Therefore, these and other studies have advocated the need for coupling neuropsychological assessments with neuroimaging techniques, and for understanding the MS cognitive status as part of the “neural efficiency hypothesis” [13,14].…”
Section: Introductionmentioning
confidence: 99%